Diagnosis of Diaphragmatic Hernia in Buffaloes : A Review - Pal, Madan; Tayal, Rishi (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
Diaphragmatic hernia is a common thoraco-abdominal disorder in adult-milch buffaloes. This disorder with its high morbidity and mortality has emerged as a major surgical condition affecting the productivity of farm animals. Increased intra-abdominal pressure due to normal heavy weight of viscera, tympany of varying degrees, advanced pregnancy and efforts at calving plays major role in inducing reticular diaphragmatic hernia in buffaloes. Signs of tympany, brisket oedema, anorexia, chronic cough, abduction of limbs, intermittent constipation or diarrhoea with small quantity of loose or scanty pasty faeces are usually present in most of the animals affected with diaphragmatic hernia. The condition is difficult to diagnose only on the basis of clinical signs and symptoms. However, imaging technique like ultrasonography can be of high diagnostic value in detecting the condition.
Keywords: Buffalo; diaphragmatic hernia; ultrasonography